Preparation method and application of all-vanadium liquid flow battery energy storage medium and its precursor
By using the method of directly dissolved vanadium oxide mixture in a fully vanadium flow battery, the problems of high equipment requirements, high energy consumption and cost in the prior art are solved, and the preparation of electrolyte with simple operation and low cost is achieved, and the performance and purity of the electrolyte are improved.
Patent Information
- Application Number
- CN202411774072.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing methods for preparing all-vana liquid flow battery electrolytes have problems such as high equipment requirements, high energy consumption and high cost, especially in the secondary transportation of concentrated sulfuric acid and sulfuric acid-containing electrolytes, the cost increases significantly.
The vanadium oxide mixture is used as the precursor and is directly dissolved in a strong acid solution. The all-vanadium liquid flow battery energy storage medium is arranged on the application site. Low-valent vanadium oxides are synthesized in one step by high-temperature solid phase method, and the reaction conditions are adjusted to prepare vanadium oxide mixtures in different proportions.
The electrolyte preparation route with simple operation and low cost is realized, which improves the purity and performance of the electrolyte and reduces energy consumption and cost in the production process.
Smart Images

Figure CN119240789B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of all-vanadium liquid flow battery energy storage medium, and more specifically, to a preparation method and application of an all-vanadium liquid flow battery energy storage medium and a precursor thereof. Background Art
[0002] Wind energy and solar energy are considered to be the cleanest renewable energy sources, but due to natural factors, they cannot obtain continuous and stable energy, and large-scale energy storage technology must be used to regulate them. However, the backwardness of energy storage technology has become a bottleneck restricting the utilization of these two renewable energy sources. All-vanadium liquid flow battery is a new type of energy storage battery with the advantages of high energy conversion efficiency, long service life, convenient capacity adjustment, high safety and environmental friendliness. It can be used in large-scale energy storage fields such as renewable energy such as solar energy and wind energy and grid peak shaving and valley filling. It is one of the most promising energy storage devices. Among them, the electrolyte as a carrier of active substances is one of the most important components of all-vanadium liquid flow batteries. The performance and concentration of the electrolyte directly affect the performance and energy density of the battery. How to obtain high-performance vanadium electrolyte has become a hot topic for researchers from various countries. There are two main methods for the synthesis of electrolytes for all-vanadium liquid flow batteries: chemical synthesis and electrolysis.
[0003] The chemical method mainly uses vanadium oxide or other vanadium salt as raw materials, heats it in a certain concentration of sulfuric acid solution and adds a reducing agent (such as S, SO2, etc.) to dissolve it and reduce it to a low-priced, easily soluble vanadium compound, thereby producing a vanadium electrolyte of a certain concentration. The advantage of the chemical synthesis method is that the production equipment is simple, but the solid dissolution rate is slow, and the added reducing agent will remain in the vanadium electrolyte and is difficult to eradicate, affecting the purity and performance of the vanadium electrolyte. The electrolysis method generally uses an electrolytic cell device with a diaphragm, using V2O5 or metavanadate as raw materials, adding an H2SO4 solution containing V2O5 or metavanadate to the negative electrode area of the electrolytic cell, adding the same concentration of H2SO4 to the positive electrode area, adding appropriate direct current to the two electrodes of the electrolytic cell, and the V2O5 or metavanadate powder is reduced on the negative electrode surface through contact with the negative electrode to produce an all-vanadium liquid flow battery electrolyte. The electrolysis method can continuously prepare high-concentration vanadium electrolyte in large quantities, is simple and convenient to operate, and is easy to carry out industrial production; in addition, the electrolysis method also has the disadvantages of slow reaction rate, high equipment requirements, high energy consumption and high cost.
[0004] In summary, the existing methods all use V2O5 to dissolve in sulfuric acid, and form a low-valent vanadium ion sulfuric acid solution through chemical or electrolytic methods. And finally make the all-vanadium liquid flow battery energy storage medium. In practical applications, it involves the secondary transportation of concentrated sulfuric acid and sulfuric acid-containing electrolyte, which greatly increases the cost. Summary of the invention
[0005] In view of the above problems, the present invention proposes a preparation method and application of an all-vanadium liquid flow battery energy storage medium and its precursor. A vanadium oxide mixture is used as a precursor, which is directly dissolved in a strong acid solution, and the all-vanadium liquid flow battery energy storage medium is directly configured at the application site, thereby realizing a method for preparing an all-vanadium liquid flow battery electrolyte that is simple, convenient to operate and low in cost.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for preparing a precursor of an all-vanadium liquid flow battery energy storage medium, comprising the following steps:
[0008] Decomposing ammonium metavanadate alone or in a mixture with a reducing agent under a high temperature inert atmosphere or under vacuum, wherein the decomposition product is a vanadium oxide mixture;
[0009] The reducing agent is a carbon material, sulfur or a carbon-containing reducing organic matter.
[0010] The reducing agent carbon material is activated carbon or graphite, and the carbon-containing reducing organic matter is melamine.
[0011] The weight ratio of the ammonium metavanadate to the reducing agent is (1-100):1;
[0012] The high temperature reaction temperature is 600°C-1000°C, and the reaction time is 1h-4h;
[0013] The high temperature inert atmosphere is argon or nitrogen inert gas.
[0014] The present invention also provides a method for preparing an all-vanadium liquid flow battery energy storage medium using the all-vanadium liquid flow battery energy storage medium precursor, comprising the following steps:
[0015] The vanadium oxide mixture is used as a precursor, dissolved in a strong acid solution, and the conditions of the dissolution reaction are controlled to prepare an all-vanadium liquid flow battery energy storage medium.
[0016] The strong acid solution is sulfuric acid and / or hydrochloric acid solution;
[0017] Furthermore, according to the ratio of vanadium oxides of different valence states in the vanadium oxide mixture, inorganic or organic substances with oxidation or reduction ability are added as additives, mixed and dissolved in sulfuric acid and / or hydrochloric acid solution, and the additives continue to oxidize or reduce the precursor vanadium oxide mixture during the dissolution process.
[0018] The additive is selected from vanadium oxide, hydrogen peroxide, potassium permanganate, sodium peroxide, oxalic acid, and glyoxal.
[0019] The weight ratio of the additive to the vanadium oxide mixture is 1:(1-10).
[0020] The concentration of the strongly acidic solution is 3M-10M.
[0021] During the dissolution reaction, the reaction temperature is 60°C-100°C, and the reaction time is 1h-5h.
[0022] The present invention also provides an all-vanadium liquid flow battery energy storage medium, which is prepared using the all-vanadium liquid flow battery energy storage medium preparation method, and the valence of vanadium ions in the obtained energy storage medium solution is configured to be trivalent or tetravalent.
[0023] The present invention also provides an application of the all-vanadium liquid flow battery energy storage medium in an all-vanadium liquid flow battery.
[0024] Advantages and effects of the present invention:
[0025] 1. The present invention provides a preparation method and application of an all-vanadium liquid flow battery energy storage medium and its precursor vanadium oxide, realizing an electrolyte preparation route that is simple to operate, convenient and low in cost.
[0026] 2. The present invention adopts a high-temperature solid phase method to synthesize the required low-valent vanadium oxide solid powder in one step. By adjusting the reaction conditions, a mixture of different low-valent vanadium oxides in different proportions can be prepared, which is suitable for the subsequent configuration of the all-vanadium liquid flow battery energy storage medium. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD pattern of the vanadium oxide mixture powder obtained after sintering in Example 1;
[0028] Figure 2 is the XRD pattern of the vanadium oxide mixture powder obtained after sintering in Example 2;
[0029] Figure 3 is the XRD pattern of the vanadium oxide mixture powder obtained after sintering in Example 3;
[0030] Figure 4 is the XRD pattern of the vanadium oxide mixture powder obtained after sintering in Example 4;
[0031] Figure 5 is the XRD pattern of the vanadium oxide mixture powder obtained after sintering in Example 5;
[0032] Figure 6 is a SEM image of the vanadium oxide mixture powder obtained after sintering in Example 1;
[0033] Figure 7 is a SEM image of the vanadium oxide mixture powder obtained after sintering in Example 2;
[0034] Figure 8is a SEM image of the vanadium oxide mixture powder obtained after sintering in Example 3;
[0035] Fig. 9 is a SEM image of the vanadium oxide mixture powder obtained after sintering in Example 4;
[0036] Fig.10 is a SEM image of the vanadium oxide mixture powder obtained after sintering in Example 5
[0037] Fig.11 is the cycle performance of the all-vanadium liquid flow battery using the energy storage medium prepared in Example 1;
[0038] Fig.12 is the cycle performance of the all-vanadium liquid flow battery using the energy storage medium prepared in Example 2;
[0039] Fig.13 is the cycle performance of the all-vanadium liquid flow battery using the energy storage medium prepared in Example 3;
[0040] Fig.14 is the cycle performance of the all-vanadium liquid flow battery using the energy storage medium prepared in Example 4;
[0041] Fig.15 The figure is the cycle performance of the all-vanadium liquid flow battery using the energy storage medium prepared in Example 5. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with embodiments. The embodiments are intended to further illustrate the present invention rather than to limit the scope of the present invention.
[0043] Example 1
[0044] The ammonium metavanadate powder was reacted at 600°C in a vacuum environment for 1 h, and then taken out after cooling to room temperature; Figure 1 The XRD pattern shows that the main valence state of the sintered powder is a mixture of trivalent and tetravalent vanadium oxides; Figure 6 The SEM image shows that the sintered powder is spherical with an average particle size of 0.5μm; the powder is directly dissolved in a 3M sulfuric acid solution and reacted at 60°C for 1h to prepare an all-vanadium liquid flow battery energy storage medium (1# solution) with a total vanadium ion concentration of 1.6M.
[0045] Solution 1# in Table 1 shows the total vanadium ion concentration and the ratio of trivalent to tetravalent vanadium ion concentrations, and no other impurity ions were detected; this solution was used to assemble an all-vanadium redox flow battery for performance testing to evaluate the electrolyte performance. The cycle performance is shown in Fig.11 And the 1# solution in Table 2, the battery efficiency and cycle stability are good.
[0046] All-vanadium liquid flow battery test conditions: positive and negative electrodes are 36cm 2Carbon felt electrode, positive and negative electrodes are made of the prepared 1# solution, using 80mA / cm 2 The charge and discharge cycle is carried out at a current density of , the charge cut-off condition is that the voltage is not higher than 1.5V, and the discharge cut-off condition is that the voltage is not lower than 0.1V.
[0047] Example 2
[0048] A mixture of ammonium metavanadate powder and sulfur as a reducing agent in a mass ratio of 1:1 was reacted at 700°C under argon gas protection for 2 hours, and then taken out after cooling to room temperature; Figure 2 The XRD diagram shows that the main valence states of the sintered powder are a mixture of trivalent and tetravalent vanadium oxides and vanadyl sulfate. Figure 7 The SEM image shows that the sintered powder is spherical with an average particle size of 0.5μm; the powder is mixed with 0.5 times the weight of the additive 5wt.% hydrogen peroxide, dissolved in 4M hydrochloric acid solution, reacted at 100℃ for 5h, and prepared into an all-vanadium liquid flow battery energy storage medium (2# solution) with a total vanadium ion concentration of 1.6M.
[0049] Solution 2 in Table 1 shows the total vanadium ion concentration and the ratio of trivalent to tetravalent vanadium ion concentrations, and no other impurity ions were detected. The all-vanadium redox flow battery was assembled with this solution for performance testing to evaluate the electrolyte performance. The cycle performance is shown in Fig.12 And the 2# solution in Table 2 has good battery efficiency and cycle stability.
[0050] All-vanadium liquid flow battery test conditions: positive and negative electrodes are 36cm 2 Carbon felt electrode, positive and negative electrodes are made of the prepared 2# solution, using 80mA / cm 2 The charge and discharge cycle is carried out at a current density of , the charge cut-off condition is that the voltage is not higher than 1.5V, and the discharge cut-off condition is that the voltage is not lower than 0.1V.
[0051] Example 3
[0052] A mixture of ammonium metavanadate powder and activated carbon as a reducing agent in a mass ratio of 10:1 was reacted at 800°C under nitrogen protection for 2 hours, and then taken out after cooling to room temperature; Figure 3 The XRD diagram shows that the main valence state of the sintered powder is a mixture of trivalent and tetravalent vanadium oxides. Figure 8 The SEM image shows that the sintered powder is spherical with an average particle size of 0.5μm; the powder is mixed with 0.1 times the weight of the additive potassium permanganate, dissolved in a mixed acid solution of 4M sulfuric acid solution and 6M hydrochloric acid, reacted at 80°C for 2h, and prepared into an all-vanadium liquid flow battery energy storage medium (3# solution) with a total vanadium ion concentration of 1.6M.
[0053] Solution 3# in Table 1 shows the total vanadium ion concentration and the ratio of trivalent to tetravalent vanadium ion concentrations, and no other impurity ions were detected; this solution was used to assemble an all-vanadium flow battery for performance testing to evaluate the electrolyte performance. The cycle performance is shown in Fig.13 And the 3# solution in Table 2 has good battery efficiency and cycle stability.
[0054] All-vanadium liquid flow battery test conditions: positive and negative electrodes are 36cm 2 Carbon felt electrode, positive and negative electrodes are made of the prepared 3# solution, using 80mA / cm 2 The charge and discharge cycle is carried out at a current density of , the charge cut-off condition is that the voltage is not higher than 1.5V, and the discharge cut-off condition is that the voltage is not lower than 0.1V.
[0055] Example 4
[0056] A mixture of ammonium metavanadate powder and reducing agent graphite in a mass ratio of 50:1 was reacted at 900°C under argon gas protection for 4 hours, and then taken out after cooling to room temperature; Figure 4 The XRD diagram shows that the main valence state of the sintered powder is a mixture of trivalent and tetravalent vanadium oxides. Fig. 9 The SEM image shows that the sintered powder is spherical with an average particle size of 0.5μm; the powder is mixed with 0.6 times the weight of the additive oxalic acid powder, dissolved in 5M sulfuric acid solution, and reacted at 70°C for 3h to prepare an all-vanadium liquid flow battery energy storage medium (4# solution) with a total vanadium ion concentration of 1.6M.
[0057] Solution 4# in Table 1 shows the total vanadium ion concentration and the ratio of trivalent to tetravalent vanadium ion concentrations, and no other impurity ions were detected. The all-vanadium redox flow battery was assembled with this solution for performance testing to evaluate the electrolyte performance. The cycle performance is shown in Fig.14 And the 4# solution in Table 2 has good battery efficiency and cycle stability.
[0058] All-vanadium liquid flow battery test conditions: positive and negative electrodes are 36cm 2 Carbon felt electrode, positive and negative electrodes are made of the prepared 4# solution, using 80mA / cm 2 The charge and discharge cycle is carried out at a current density of , the charge cut-off condition is that the voltage is not higher than 1.5V, and the discharge cut-off condition is that the voltage is not lower than 0.1V.
[0059] Example 5
[0060] A mixture of ammonium metavanadate powder and reducing agent melamine in a mass ratio of 100:1 was reacted at 1000°C under vacuum gas protection for 3 hours, and then taken out after cooling to room temperature; Figure 5 The XRD diagram shows that the main valence state of the sintered powder is a mixture of trivalent and tetravalent vanadium oxides. Fig.10The SEM image shows that the sintered powder is spherical with an average particle size of 0.5μm; the powder is mixed with the same weight of the additive vanadium pentoxide, dissolved in 6M sulfuric acid solution, and reacted at 60°C for 3h to prepare an all-vanadium liquid flow battery energy storage medium (5# solution) with a total vanadium ion concentration of 1.6M.
[0061] Solution 5# in Table 1 shows the total vanadium ion concentration and the ratio of trivalent to tetravalent vanadium ion concentrations, and no other impurity ions were detected. The all-vanadium redox flow battery was assembled with this solution for performance testing to evaluate the electrolyte performance. The cycle performance is shown in Fig.15 And the 5# solution in Table 2 has good battery efficiency and cycle stability.
[0062] All-vanadium liquid flow battery test conditions: positive and negative electrodes are 36cm 2 Carbon felt electrode, positive and negative electrodes are made of the prepared 5# solution, using 80mA / cm 2 The charge and discharge cycle is carried out at a current density of , the charge cut-off condition is that the voltage is not higher than 1.5V, and the discharge cut-off condition is that the voltage is not lower than 0.1V.
[0063] Table 1 Ion concentration of energy storage medium in Examples 1-5
[0064]
[0065] Table 2 Cyclic performance of energy storage media in Examples 1-5
[0066]
[0067] It can be found from the data in the table that the all-vanadium liquid flow battery energy storage medium synthesized by this method can be applied to all-vanadium liquid flow batteries to obtain higher coulombic efficiency and energy efficiency.
Claims
1. A method for preparing a precursor of an all-vanadium liquid flow battery energy storage medium, characterized in that: The following steps are involved: Decomposing a mixture of ammonium metavanadate and a reducing agent under high temperature inert atmosphere or vacuum, wherein the decomposition product is a mixture of trivalent and tetravalent vanadium oxides; The reducing agent is a carbon material, sulfur or a carbon-containing reducing organic matter; the carbon material is activated carbon or graphite, and the carbon-containing reducing organic matter is melamine.
2. The method for preparing a precursor of an all-vanadium liquid flow battery energy storage medium as claimed in claim 1, characterized in that: The weight ratio of the ammonium metavanadate to the reducing agent is (1-100):1; The high temperature reaction temperature is 600°C-1000°C, and the reaction time is 1h-4h; The high temperature inert atmosphere is argon or nitrogen inert gas.
3. A method for preparing an all-vanadium liquid flow battery energy storage medium using the all-vanadium liquid flow battery energy storage medium precursor according to claim 1, characterized in that: The following steps are involved: The vanadium oxide mixture is used as a precursor, and inorganic or organic substances with oxidation or reduction ability are added as additives according to the ratio of vanadium oxides of different valence states in the vanadium oxide mixture. The mixture is mixed and dissolved in a sulfuric acid and / or hydrochloric acid solution. The additive continues to oxidize or reduce the precursor vanadium oxide mixture during the dissolution reaction, and the conditions of the dissolution reaction are controlled to configure the all-vanadium liquid flow battery energy storage medium.
4. The method for preparing the all-vanadium liquid flow battery energy storage medium according to claim 3, characterized in that: The additive is selected from vanadium oxide, hydrogen peroxide, potassium permanganate, sodium peroxide, oxalic acid, and glyoxal.
5. The method for preparing the all-vanadium liquid flow battery energy storage medium according to claim 3, characterized in that: The weight ratio of the additive to the vanadium oxide mixture is 1:(1-10); The concentration of the strongly acidic solution is 3M-10M.
6. The method for preparing the all-vanadium liquid flow battery energy storage medium according to claim 3, characterized in that: During the dissolution reaction, the reaction temperature is 60°C-100°C, and the reaction time is 1h-5h.
7. An all-vanadium liquid flow battery energy storage medium, characterized in that: The preparation is carried out using the preparation method of the all-vanadium liquid flow battery energy storage medium as described in claim 6, and the valence of the vanadium ions in the obtained energy storage medium solution is configured to be trivalent or tetravalent.
8. Use of the all-vanadium liquid flow battery energy storage medium according to claim 7 in an all-vanadium liquid flow battery.
Citation Information
Patent Citations
Method for preparing electrolyte of vanadium flow battery
CN102468508A
All-vanadium redox flow battery electrolyte and preparation method thereof
CN116154244A
Method for preparing 3.5-valent vanadyl sulfate electrolyte in short process
CN116995285A
KR20220093660A